2021
DOI: 10.18485/epmj.2021.11.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Workplace Spirituality on Project Team Creativity with Mediating Role of Project Team Prudence and Project Team Virtue

Abstract: Purpose of this research is to investigate the impact of workplace spirituality on project team creativity and the mediating role of project team prudence & project team virtue between workplace spirituality and project team creativity. The data for this study has been collected from Telecommunication Services Provider Industry of Pakistan. We tested the effect of workplace spirituality on project team creativity and further examined the mediating effects of project team prudence & project team virtue between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Spirituality has been explored for decades by scholars and researchers across many academic disciplines such as adult education (Tisdell, 2006(Tisdell, , 2008 and management (Nicolae et al, 2013;Pandey & Gupta, 2008), involving the topics of organizational performance (Garg, 2020), organizational culture (Chalofsky & Cavallaro, 2013;Hisam & Sanyal, 2021), employee performance and behavior (Jena, 2021;Osman-Gani & Anwar, 2014), corporate social responsibility (CSR) (Afsar & Umrani, 2020), organizational citizenship behavior (Anwar & Osman-Gani, 2015), and across cultures (Ali & Rehman, 2021). Fry and Nisiewicz (2013) explained that a person's spirit is a very powerful force of inner life with a desire to connect with others and to give meaning to their life and work, and is driven by hope, faith, and self-transcendence or wholeness.…”
Section: Spiritualitymentioning
confidence: 99%
See 4 more Smart Citations
“…Spirituality has been explored for decades by scholars and researchers across many academic disciplines such as adult education (Tisdell, 2006(Tisdell, , 2008 and management (Nicolae et al, 2013;Pandey & Gupta, 2008), involving the topics of organizational performance (Garg, 2020), organizational culture (Chalofsky & Cavallaro, 2013;Hisam & Sanyal, 2021), employee performance and behavior (Jena, 2021;Osman-Gani & Anwar, 2014), corporate social responsibility (CSR) (Afsar & Umrani, 2020), organizational citizenship behavior (Anwar & Osman-Gani, 2015), and across cultures (Ali & Rehman, 2021). Fry and Nisiewicz (2013) explained that a person's spirit is a very powerful force of inner life with a desire to connect with others and to give meaning to their life and work, and is driven by hope, faith, and self-transcendence or wholeness.…”
Section: Spiritualitymentioning
confidence: 99%
“…Li et al (2014) observed that this change in workforce structure calls for further research on team member behaviors that effect team productivity and team member motivation. Given the prevalence and increasing use of work teams (Salas et al, 2018), a better understanding of how individuals express and experience WS in their work teams is warranted because limited empirical research is available on the topic of WS and even less research has examined WS within the context of work teams (Ali & Rehman, 2021). Therefore, to address these shortcomings, the purpose of this study was to better understand how individuals express and experience WS within their work teams and how their WS influences their work teams.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations